Pengaruh Perubahan Organisasi dan Budaya Organisasi terhadap Kepuasan dan Kinerja Karyawan - Franadita, Dwi; Aslami, Nuri (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study was to analyze the effect of organizational culture, job satisfaction, and organizational commitment on employee performance. The research object chosen in this study is the method of this research is the study of literature. The results of this study prove and conclude that: (1) organizational culture has a positive and significant effect on job satisfaction, (2) organizational culture has a positive and significant effect on organizational commitment, (3) job satisfaction has a positive and significant effect on organizational commitment, ( 4) organizational commitment has a positive and significant effect on employee performance, (5) organizational culture has a positive and significant effect on employee performance.